Grand Timely Topics in Software Engineering: International Summer School GTTSE 2015, Braga, Portugal, August 23-29, 2015, Tutorial Lectures - Cunha, Jácome; Fernandes, João P; Lämmel, Ralf; Saraiva, João; Zaytsev, Vadim (Lecture Notes in Computer Science, 2017)
This tutorial volume includes the revised and extended tutorials (briefings) held at the 5th International Summer School on Grand Timely Topics in Software Engineering, GTTSE 2015, in Braga, Portugal, in August 2015. GTTSE 2015 applied a broader scope to include additional areas of software analysis, empirical research, modularity, and product lines. The tutorials/briefings cover probabilistic program analysis, ontologies in software engineering, empirical evaluation of programming and programming languages, model synchronization management of software product families, "people analytics" in software development, DSLs in robotics, structured program generation techniques, advanced aspects of software refactoring, and name binding in language implementation.